Problems related to the incidence of whiteflies as pests of annual crops in the cauca Valley of Colombia - RODRÍGUEZ, ISAURA V.; CARDONA, CÉSAR (Revista Colombiana de Entomología, 2001)
A diagnostic survey on the incidence and importance of whiteflies as pests of annual crops was conducted in the Cauca Valley Department of Colombia. To identify species and biotypes of these insects, 78 biological samples were taken in 15 different localities. Samples were taken to the laboratory and the species and biotypes were identified by means of fourth instar morphology, electrophoresis for a-esterases, and RAPD-PCR analysis. Insecticide use patterns were determined by interviewing 56 farmers. Trialeurodes vaporariorum (Westwood) (73% of total samples taken) was the predominant species attacking tomatoes, snap beans, cucumber, squash, eggplant, dry beans. and pepper. The biotype of Bemisia tabaci (Gennadius) (15.5% of samples taken) was found on cotton and soybeans. The B biotype, also known as B. argentifolii Bellows and Perring, (11.5%) was registered as a pest of poinsettias grown under greenhouse conditions. Farmers are using 30 different active ingredients of insecticides to control whiteflies. Of these, 46% are organophosphates, 23% are insect growth regulators, 20% are carbamates, and 10% are pyrethroids. The mean number of applications per cropping season is 10. Ali farmers spray on a preventative basis with little or no regard for pest infestation levels. Tomato is the most heavily sprayed crop, usually every 2-3 days. Few farmers (14%) receive some kind of technical assistance and 71 % do not take precautionary measures when using toxic insecticides.